The Concept of Unity in Plato and Kant - Burovas, Valerijus (Problemos, 1979)
The article presents a treatment of the concept of unity in Kant’s philosophy from two angles. On the one hand, the concept of unity is viewed against the background of the idea of apriority, in its initial conception of the criterion up to its development into the method of transcendental gnoseology. On the other hand, this problem is analysed in relation with the idea of critical treatment of the mind concerning its independent a priori knowledge. Irrespective of the fact that Kant’s idealism is subjective, whereas that of Plato is objective, the problem of unity is treated somewhat analogously in their works. This is discovered in the analysis of relations between the ideal and the real in gnoseological and ontological approaches in Kant and Plato, respectively.